Coping capacity of households to Rift Valley fever case study: Ijara District, Kenya - Kiplimo, Jusper Ronoh; Waithaka, H.E.; Notenbaert, An Maria Omer; Bett, Bernard K. (2013)
East-Africa is highly vulnerable to climate variability and adverse effects of climate change. This has made it a challenge to predictors of early warning systems. Extended and above normal rainfall across arid and semi-arid Africa after a warm phase of El Niño creates conditions favourable for outbreak of Rift Valley Fever (RVF). There have been two major outbreaks in the Horn of Africa in 1997/98 and 2006/07 that had the highest mortality to both humans and livestock causing huge economic losses. RVF is a vector borne disease transmitted by a variety of mosquito species to humans and domestic animals. The disease causes abortions in domestic animals and mortality to both animals and human beings. The virus is common in sheep and cattle with secondary transmission to humans by mosquitoes and handling and consumption of infected livestock. In Kenya, the recent outbreak occurred in December 2006 to March 2007 which was confirmed by entomological and epidemiological field investigation of virus activity in areas identified at risk. The first case was reported in Garissa in early December 2006 and later antibodies were detected in blood serum from 10 humans that coincided with livestock RVF confirmations. This outbreak was the worst in history with a record death of 75 people in a span of 3 months with approximately 180 humans being affected in the whole of North Eastern. In the entire period markets remained closed for fear of further outbreak. Our study evaluates areas through an integrated geostatistical analysis where are the risk areas in Ijara, Kenya. Ijara District is one of the eleven districts that form the North Eastern Province.The site has in the past and still is the Rift Valley Fever high risk area. It lies approximately 33oE 6oN, and 43oE 5oS and is devoid of mountains. It is characterized by low undulating plains that have low-lying altitude ranging between zero and 90 metres above sea level. Utilization of remote sensing products makes it possible to capture the anomalous warming and onset of extended rainfall.This is useful to confirming episodic RVF outbreaks. Vegetation green up accompanied on precipitation has been found to be a major influence to abundance of vector populations. The vegetation green up will be determined by normalized difference vegetation index, an indicator of health of vegetation. For the ideal conditions to be created then topography and geology would be other factors to consider in space and water retention capacity respectively. All the above considered it is possible to map and utilize time series measurements to map and predict specific areas at elevated risk for RVF. The study elicits coping strategies, by way of field work, that communities have adopted to make them less exposed to Rift Valley Fever outbreaks. Coping strategies have in the past been known to influence household come community characteristics to absorb shocks that could adversely change their livelihood socially and economically. The choice of coping strategies determines the ability they have to deal with adverse climate variability and outbreaks of diseases like RVF. Then by statistical analysis evaluate which coping strategies make the communities less vulnerable to adverse climatic variability and disease outbreaks. The study also elicits which of the coping strategies adopted by the communities would require information sharing and empowerment of policy makers socio-economically.